The Role of Influencer Engagement towards Online Buying Intention - Salim, Siti Aisyah; Roslan, Nur Iwani (Research in Management of Technology and Business, 2022)
Influencer engagement is a process where communication, sharing feeling, thoughts, and experiences with followers with the intention to connect with the influencers in social media platform. Though influencer engagement is one of the popular strategies, influencers that lack of capacity to generate compelling content may fail to connect with the retailer’s target audiences which mean less intention to buy online. The current studies also just focus on the interaction between influencers and their followers from the perspective of influencer role as a seller with lacking research on follower’s perspectives especially in the context of Gen Z in Malaysia. Hence, this research aims to identify the level of influencer engagement towards buying intention, the level of buying intention, and the relationship between the level of influencer engagement and buying intention. The Human Brand Model is adopted as the theoretical foundation in this research. This study has collected data from 100 respondents among Gen Z students in UTHM. The sample collected based on a quantitative research method where a self-administrated questionnaire and online survey will be applied. All the collected data were analyzed using Statistical Package for Social Science (SPSS) to develop the quantitative reports presented in the form of frequency, percentage, mean and standard deviation. This study helps marketers to understand the best marketing strategy to adopt especially for Gen Z. As a result, all variables have a significant relationship with online buying intention and Ideality refers to the influencers’ engagement that can give a good visual in branding and marketing has the highest correlation coefficient of 0.542.